===========================================================
Explanation:
The preimage (-6,-2) shifts to the image point (-4,-4)
Focus on the x coordinates. The jump from -6 to -4 is an increase of 2. So we have x become x+2
Now focus on the y coordinates. The jump from -2 to -4 is -2, so y becomes y-2
The translation rule we use is [tex](\text{x},\text{y})\to (\text{x}+2,\text{y}-2)[/tex] which shifts the point 2 units to the right and 2 units down.
-----------------
Let's apply this rule to the point (3,-1)
[tex](\text{x},\text{y})\to (\text{x}+2,\text{y}-2)\\\\(3,-1)\to (3+2,-1-2)\\\\(3,-1)\to \boldsymbol{(5,-3)}\\\\[/tex]
The preimage (3,-1) shifts to the image (5, -3)